DIGITAL INFORMATION RESOURCES AND SERVICES IN MANAGEMENT INSTITUTE LIBRARIES: A STUDY WITH SPECIAL REFERENCE TO KERALA - Ramya Raveendran and A.T. Francis (Library Progress(International)., 2014)
The Paper is based on a study conducted in the libraries of management institutes in Kerala. The objectives of the study were, viz., 1. To understand the current status of Digital information resources and services provided by the Management Institute Libraries in Kerala; 2. To benchmark the management institute libraries in Kerala with IIM-Kozhikode in terms of Digital Library Facilities and Services; 3. To understand the status of digitalized resources in the Management Institute Libraries; and 4. To assess the shortfalls of the existing Library Information System and Services utilized by the Management Institute Libraries. The study covering all the Management Institutes of Kerala and data was collected through the websites of the Institutes or the concerned Library . The study revealed that the Management Institute Libraries in Kerala give only less importance in providing digitalized Information Resources and Services to the different category of users in comparison with the global standard . It also thrown light to the fact they have to put serious efforts in order to provide full fledged digitalized knowledge products and services to the users.